A GLOBAL SCIENTOMETRIC ANALYSIS OF HERPES ENCEPHALITIS RESEARCH IN THE LAST 50 YEARS - Yildirim, İrem; Alkan, Sevil (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Herpes encephalitis is the most common of all encephalitis worldwide and has the highest mortality rate. The aim of this study is to review articles on this topic in order to provide a guide for future herpes encephalitis studies to assess current publishing trends and hotspots on herpes encephalitis research globally. Objective: People have been affected by the herpes virus for many years, but advances in supportive care and antiviral drugs have only recently made it possible for doctors to treat the most severe types of infections. To the authors' knowledge, however, no bibliometric analysis has been done to rate Herpes encephalitis research. In order to enhance research in this area, this study used a bibliometric analysis to assess current publishing trends and hotspots on herpes encephalitis research globally. Methods: The Web of Science database was searched for pertinent publications between January 1970 and December 2021. The research points, comprising publishing countries, affiliations, first authors, cited authors, cited references, and their clustering, as well as keyword co-occurence, were analyzed using VosViewer to identify research trends and hotspots. Results: The results of this study's search methodology revealed that between 1970 and 2021, 2138 documents. Only articles (n=1223) were included the study. 89.37% of the articles were written in English. The first article published in 1970 and most of the articles published in the years 1982, 1988, 2007, 2016, and 2017. The United States of America (USA) (29.109%), England (9.076%), France (7.441%), Japan (7.359%) and Germany (7.032) were the other top ranked countries. The most citation numbers were recorded in the year 2021. Conclusion: This bibliometric analysis outlined the general overview for Herpes encephalitis research and offered insightful guidance for continuing investigations.